A cross sectional study on tobacco usage among COVID 19 Positive patients admitted in a tertiary care centre in Mizoram India - Ralte, Jane R; Hrahsel, Lalrinawmi; Sailo, Lalnuntluanga; Anusuya, Ganesh Shanmugasundaram; Sailo, Lalnunmawii; Ruata, Lalrem (Asian Journal of Medical Sciences, 2023)
Background: Mizoram is one of the states in India with the high prevalence of tobacco usage both in terms of smoke form and smokeless form. In spite of high prevalence of smoking, the state has reported less COVID-19 related mortality. The prevalence of tobacco usage among the COVID-19 positive patients and its relation to clinical symptoms and mortality has not been studied in North East part of India. Aims and Objectives: The aim of the study was to study the association of tobacco usage and its relation to clinical symptoms and mortality in COVID-19 patients. Materials and Methods: A total of 100 COVID 19 positive patients admitted in wards of Zoram Medical College, Mizoram between June and August 2020 were selected using convenient sampling. The patients were interviewed over mobile phone after getting informed oral consent. The details regarding socio-demographic variables, tobacco usage, co morbidities, and clinical symptoms were collected from the patients. Comorbidities and smoking were considered as primary outcome variables. The mean values were compared between study groups using independent sample t-test (two groups). Categorical outcomes were compared between study groups using Chi-square test/Fisher’s Exact test (If the overall sample size was <20 or if the expected number in any one of the cells is <5), Fisher’s exact test was used. Results: Out of 100 patients, 54% were males, the mean age was 27.71 years. Recent history of travel was noted in 82% and 12% had history of contact with positive case. Smokers were 42% and 36% were past smokers. The various other forms of tobacco products used were Gutkha (10%), Tuibur (3%), Sahdah (13%), and Kuhva (52%). About 37% were symptomatic. The common symptoms observed were fever (19%), cough (14%), body pain (9%), and sore throat (9%). Only 4% had difficulty in breathing. 19 (45.24%) of the smokers were symptomatic while 18 (31.03%) were symptomatic among nonsmokers (P=0.092). Mortality was 0% among our study population. Conclusion: The present study showed that symptomatic patients were more among smokers when compared with nonsmokers, but the findings were not statistically significant. Hence, further studies needed to be done in this area with a larger sample size.